A Survey of Occupational Therapists on a New Tool for Sensory Processing - Caroline J. Mills; Elisabeth Michail; Rosalind A. Bye (Occupational Therapy International)
Occupational therapy is the leading profession with regard to supporting children who experience difficulties with occupations as a result of sensory processing differences. However, there are mixed reports with regard to the efficacy of various sensory interventions and approaches, leaving little clear guidance for occupational therapists supporting children with these difficulties. The Sensory Form is a planning tool developed in 2017 to guide occupational therapists in their professional reasoning for assessment and intervention of sensory processing differences. To date, no research has been conducted on its use. Researchers introduced the tool to 20 occupational therapists with relevant experience and conducted an online survey of their perceptions about The Sensory Form. Findings were analysed using descriptive statistics and qualitative content analysis. Therapists reported that they found the tool acceptable for use, described key strengths and weaknesses of The Sensory Form, and outlined changes to improve the tool. The Sensory Form may have an application in guiding the practice of therapists supporting children with sensory processing differences. Further development of associated resources may be warranted.